Decentralization of the health system - experiences from Pakistan, Portugal and Brazil - Shafaq Mahmood; Rita Sequeira; Muhammad Muneeb Ullah Siddiqui; Marcos Batista Araujo Herkenhoff; Patrícia Pita Ferreira; Adalberto Campos Fernandes; Paulo Sousa (BMC, 2024)
Abstract Background Decentralization of a health system is a complex and multidimensional phenomenon that demands thorough investigation of its process logistics, predisposing factors and implementation mechanisms, within the broader socio-political environment of each nation. Despite its wide adoption across both high-income countries (HICs) and low-and-middle-income countries (LMICs), empirical evidence of whether decentralization actually translates into improved health system performance remains inconclusive and controversial. This paper aims to provide a comprehensive description of the decentralization processes in three countries at different stages of their decentralization strategies - Pakistan, Brazil and Portugal. Main body This study employed a systematic analysis of peer-reviewed academic journals, official government reports, policy documents and publications from international organizations related to health system decentralization. A comprehensive search was conducted using reputable databases such as PubMed, Google Scholar, the WHO repository and other relevant databases, covering the period up to the knowledge cutoff date in June 2023. Information was systematically extracted and organized into the determinants, process mechanics and challenges encountered during the planning, implementation and post-decentralization phases. Although decentralization reforms have achieved some success, challenges persist in their implementation. Comparing all three countries, it was evident that all three have prioritized health in their decentralization reforms and aimed to enhance local decision-making power. Brazil has made significant progress in implementing decentralization reforms, while Portugal and Pakistan are still in the process. Pakistan has faced significant implementation challenges, including capacity-building, resource allocation, resistance to change and inequity in access to care. Brazil and Portugal have also faced challenges, but to a lesser extent. The extent, progress and challenges in the decentralization processes vary among the three countries, each requiring ongoing evaluation and improvement to achieve the desired outcomes. Conclusion Notable differences exist in the extent of decentralization, the challenges faced during implementation and inequality in access to care between the three countries. It is important for Portugal, Brazil and Pakistan to address these through reinforcing implementation strategies, tackling inequalities in access to care and enhancing monitoring and evaluation mechanism. Additionally, fostering knowledge sharing among these different countries will be instrumental in facilitating mutual learning.